The fifth subunit of the (α4β2)(2)β2 nicotinic ACh receptor modulates maximal ACh responses - New, Karina (Br J Pharmacol, 2017)
BACKGROUND AND PURPOSE: The fifth subunit in the (α4β2)(2)α4 nicotinic ACh receptor (nAChR) plays a determining role in the pharmacology of this nAChR type. Here, we have examined the role of the fifth subunit in the ACh responses of the (α4β2)(2)β2 nAChR type. EXPERIMENTAL APPROACH: The role of the fifth subunit in receptor function was explored using two‐electrode voltage clamp electrophysiology, along with subunit‐targeted mutagenesis and the substituted cysteine scanning method applied to fully linked (α4β2)(2)β2 receptors. KEY RESULTS: Covalent modification of the cysteine‐substituted fifth subunit with a thiol‐reactive agent (MTS) caused irreversible inhibition of receptor function. ACh reduced the rate of the reaction to MTS, but the competitive inhibitor dihydro‐β‐erythroidine had no effect. Alanine substitution of conserved residues that line the core of the agonist sites on α4(+)/β2(−) interfaces did not impair receptor function. However, impairment of agonist binding to α4(+)/β2(−) agonist sites by mutagenesis modified the effect of ACh on the rate of the reaction to MTS. The extent of this effect was dependent on the position of the agonist site relative to the fifth subunit. CONCLUSIONS AND IMPLICATIONS: The fifth subunit in the (α4β2)(2)β2 receptor isoform modulates maximal ACh responses. This effect appears to be driven by a modulatory, and asymmetric, association with the α4(+)/β2(−) agonist sites. LINKED ARTICLES: This article is part of a themed section on Nicotinic Acetylcholine Receptors. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.11/issuetoc